2018
DOI: 10.1002/cne.24489
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of sonic hedgehog and notch signaling in regenerative neurogenesis in adult zebrafish optic tectum after stab injury

Abstract: Unlike humans and other mammals, adult zebrafish have the superior capability to recover from central nervous system (CNS) injury. We previously found that proliferation of radial glia (RG) is induced in response to stab injury in optic tectum and that new neurons are generated from RG after stab injury. However, molecular mechanisms which regulate proliferation and differentiation of RG are not well known. In the present study, we investigated Shh and Notch signaling as potential mechanisms regulating regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 54 publications
2
22
1
Order By: Relevance
“…No significant change of neuron production from injury-induced proliferative RG labeled during 1–3 dpi is observed (Figure 7H, J, K, O and P). Ueda et al recently showed that Notch inhibition during 4–7 dpi decreases the number of newborn neurons (Ueda et al, 2018), which is in contrast to our findings. This inconsistency is likely to be because the time window of EdU or BrdU treatment is different.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No significant change of neuron production from injury-induced proliferative RG labeled during 1–3 dpi is observed (Figure 7H, J, K, O and P). Ueda et al recently showed that Notch inhibition during 4–7 dpi decreases the number of newborn neurons (Ueda et al, 2018), which is in contrast to our findings. This inconsistency is likely to be because the time window of EdU or BrdU treatment is different.…”
Section: Discussioncontrasting
confidence: 99%
“…RO4929097, another Notch signaling inhibitor, resulted in a similar phenotype (Figure 5—figure supplement 1A–D). Consistent with the findings of a recent study (Ueda et al, 2018), Notch inhibition was also sufficient to trigger the proliferation of tectal RG even without any injury (DMSO-treated: 6.3 ± 0.48 cells, n = 4; LY411575-treated: 26.7 ± 2.4 cells, n = 5; mean ± SEM; p>0.05; Figure 5D, E, H, I, J, Figure 5—figure supplement 1C and D), which was reminiscent of the increase of constitutively proliferative RG in the zebrafish telencephalon by Notch inhibition (Chapouton et al, 2010).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This ability to hold numerous cells in a proliferating stage allows for the recruitment of stem-progenitor cells to multiply and migrate following damage to brain tissue in order to allow cells to then remodel the brain environment in a regenerative fashion 8 , 9 . While much of our knowledge about the regenerative capacity of the adult zebrafish brain have come from invasive stab lesion studies 8 11 , few studies have investigated the zebrafish ability to regenerate a specific neuronal subtype through a conditional and specific ablation approach in the adult brain.…”
Section: Introductionmentioning
confidence: 99%